2016
DOI: 10.18632/oncotarget.8497
|View full text |Cite
|
Sign up to set email alerts
|

CGP57380 enhances efficacy of RAD001 in non-small cell lung cancer through abrogating mTOR inhibition-induced phosphorylation of eIF4E and activating mitochondrial apoptotic pathway

Abstract: The mammalian target of rapamycin (mTOR) is a potentially important therapeutic target in a broad range of cancer types. mTOR inhibitors such as rapamycin and its analogs (rapalogs) have been proven effective as anticancer agents in non-small cell lung cancer (NSCLC), whereas they strongly enhance phosphorylation of eukaryotic translation initiation factor 4E (eIF4E) and activation of Akt, which cause resistance to mTOR-targeted therapy after an initial response. Rapamycin induces eIF4E phosphorylation by acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…We exposed a range of NPC cell lines and immortalized normal nasopharyngeal epithelial cell line to CGP57380 and observed that targeting the MNK-eIF4E axis by CGP57380 treatment decreased their proliferation and colony-forming ability with little apparent toxicity to the immortalized normal nasopharyngeal epithelial cell line, which was consistent with previous investigations in blast crisis chronic myeloid leukemia and NSCLC 18, 51. Paradoxically, when expression of p-MNK1 and p-eIF4E was inhibited by CGP57380, the expression of total β-catenin was stimulated but the downstream targets of β-catenin signaling, including cyclin D1, c-Myc, MMP-7, and Axin2, were suppressed in a time- and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 86%
“…We exposed a range of NPC cell lines and immortalized normal nasopharyngeal epithelial cell line to CGP57380 and observed that targeting the MNK-eIF4E axis by CGP57380 treatment decreased their proliferation and colony-forming ability with little apparent toxicity to the immortalized normal nasopharyngeal epithelial cell line, which was consistent with previous investigations in blast crisis chronic myeloid leukemia and NSCLC 18, 51. Paradoxically, when expression of p-MNK1 and p-eIF4E was inhibited by CGP57380, the expression of total β-catenin was stimulated but the downstream targets of β-catenin signaling, including cyclin D1, c-Myc, MMP-7, and Axin2, were suppressed in a time- and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study also found that the MNK inhibitor, CGP57380, attenuates RAD001-activated eIF4E phosphorylation in non-small-cell lung cancer cells. Such a combination of inhibitors augmented the antitumor response by inhibiting cell proliferation and inducing apoptosis [98].…”
Section: Interplay Between the Mtor And Mnk/eif4e Pathwaysmentioning
confidence: 99%
“…The aberrant expression of mTor has been shown to be essential for the tumorigenesis of the majority of all cancers [811], including OS [12]. Recently, the membrane-associated E3 ubiquitin ligase ZNRF2 has been shown to be involved in the activation and regulation of mTor through protein interaction [13].…”
Section: Introductionmentioning
confidence: 99%